2022
DOI: 10.1002/ejp.1957
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term observational studies with cannabis‐based medicines for chronic non‐cancer pain: A systematic review and meta‐analysis of effectiveness and safety

Abstract: Background and Objective: This systematic review evaluated the effectiveness, tolerability and safety of cannabis-based medicines (CbMs) for chronic noncancer pain (CNCP) in long-term observational studies.Databases and Data Treatment: CENTRAL, EMBASE and MEDLINE were searched until December 2021. We included prospective observational studies with a study duration ≥26 weeks. Pooled estimates of event rates of categorical data and standardized mean differences (SMD) of continuous variables were calculated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 51 publications
(58 reference statements)
2
20
0
4
Order By: Relevance
“…Although these results support the efficacy and safety of medical cannabis therapy as an alternative to opioid management, more studies are needed to determine the appropriate dosage, timing, and method of administration. Recent systematic reviews investigating the safety and efficacy of medical cannabinoid therapy for chronic pain have found that the certainty of evidence is low [ 17 , 18 ]. Of these reviews, one study stated that 20.8% of the patients reported a reduction in half or more of their pain and 3% of patients reported serious adverse events [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these results support the efficacy and safety of medical cannabis therapy as an alternative to opioid management, more studies are needed to determine the appropriate dosage, timing, and method of administration. Recent systematic reviews investigating the safety and efficacy of medical cannabinoid therapy for chronic pain have found that the certainty of evidence is low [ 17 , 18 ]. Of these reviews, one study stated that 20.8% of the patients reported a reduction in half or more of their pain and 3% of patients reported serious adverse events [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews investigating the safety and efficacy of medical cannabinoid therapy for chronic pain have found that the certainty of evidence is low [ 17 , 18 ]. Of these reviews, one study stated that 20.8% of the patients reported a reduction in half or more of their pain and 3% of patients reported serious adverse events [ 17 ]. In the study, serious adverse events were defined as an event leading to hospitalization or death [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the analgesic effect was small and with limited clinical significance, while the efficacy in pain reduction was similar between patients affected by neuropathic or non-neuropathic chronic pain. Moreover, the evidence was in general moderate to low, and meta-analyses included both CPP and chronic secondary pain, without differentiating these different conditions, with the majority of included studies having enrolled patients with the latter condition [11][12][13][14][15][16][17][18]. Also, other systematic reviews evaluated and included studies without comparators [17,19], which may limit the possibility to evaluate the presence of the placebo effect and thus estimate the real efficacy or effectiveness of cannabinoids.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the evidence was in general moderate to low, and meta-analyses included both CPP and chronic secondary pain, without differentiating these different conditions, with the majority of included studies having enrolled patients with the latter condition [11][12][13][14][15][16][17][18]. Also, other systematic reviews evaluated and included studies without comparators [17,19], which may limit the possibility to evaluate the presence of the placebo effect and thus estimate the real efficacy or effectiveness of cannabinoids. Albeit limited by some clinical and methodological constraints, recent studies and systematic reviews on fibromyalgia suggested that cannabinoids might be useful and safe in the treatment of CPP [20][21][22].…”
Section: Introductionmentioning
confidence: 99%